THE INFLUENCE OF LEARNING MODEL OF JIGSAW WITH FLASHCARD TOWARD MOTIVATION AND BIOLOGY LEARNING RESULT OF CLASS XI STUDENTS IN SMAN 2 LOA JANAN. - Setyaningsih, Sulis; Masruhim, Muh Amir; Rambitan, Vandalita Maria Magdalena (Journal of Biology Education, 2017)
The purpose of this research is to know the influence of cooperative learning model of jigsaw type with flashcard media toward motivation and biology learning result of class XI students in SMAN 2 Loa Janan. This type of research is Quassy Experiment with non-equivalent pretest-posttest control group design research where there are experimental class and control class which are each given pretest and posttest. The sample of this research are the students of class XI SMAN 2 Loa Janan that were both in experiment and control class are 28 people. Data analysis technique used independent samples t-test, paired t-test and manova test. Student learning motivation on applying cooperative learning model of jigsaw type and flashcard media is significantly different with conventional learning with significance value < ? (0,000 < 0,05). Student learning outcomes on the application of cooperative learning model type jigsaw and flashcard media is significantly different from conventional learning with significance value < ? (0,001 < 0,05). The application of cooperative learning model of jigsaw type and flashcard media has a significant effect on students' motivation and learning outcomes with a significance value of 0,000 (0,000 <0.05) which means very significant effect.